PELAKSANAAN PENGENDALIAN PENYAKIT KRESEK PADA TANAMAN PADI DENGAN MENGGUNAKAN BIOFUNGISIDA - Sakir, Icuk Muhammad; Desinta, Desinta (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2025)
The aim of this empowerment is to control crackle disease in rice plants using biofungicides. Disease control in rice plants can be done in various ways, one of which is by using biofungicides. The movement to control (Gerdal) crackle disease was carried out by the Mawar farmer group, Tanjung Pasir Village, Pemulutan District, Ogan Ilir Regency. The number of members of the farmer group carrying out the control movement was 30 people, and was assisted by 10 officers from extension officers and Plant Pest Organism Control Officers (POPT). The control area is 10 hectares with rice plants of the Ciherang variety with an attack intensity of 2.5%. Implementation of activities starts from 07.00 am until finished on rice plants that are still 55-60 days after planting (DAP). The methods of implementing activities are (a) socialization; (b) implementation; and (c) community participation. The results of community empowerment activities show that the use of specially formulated microbial fungicides to combat plant diseases such as bacterial leaf blight (kresek), rice blast, bacterial wilt, fusarium wilt, and powdery mildew can reduce the intensity of attacks on rice plants.